Commitment to Employer and Union: Effects of Membership Status - Conlon, Edward J.; Gallagher, Daniel G. (Academy of Management Journal, 1987)
The article discusses the loyalty of employees to their employers and to labor unions. According to the author, prior research into this matter fails to consider whether or not union membership is voluntary, as well as the varying levels of union commitment. The author notes that this study examines the level of employee commitment to a union, the level of commitment to an employer and the correlation of these two measures across three identified subgroups: union members, nonmembers who have never been members and nonmembers who have left the union.